Area-Based Mechanism for Empowerment Persons with Disabilities in 3 Southern Border Provinces - Neelapaijit, Adam; Visuttipun, Paranee; Ratchatawan, Warangkana (Princess of Naradhiwas University Journal, 2021)
The purposes of the research were: (1) to study the area-based mechanism for empowerment persons with disabilities and (2) to do the case study of persons with disabilities on the quality of life in 3 southern border provinces of Thailand by following the standard indicators of quality of life for persons with disabilities in 3 southern border provinces of Thailand. The Population and sample consisted of 12 people working with persons with disabilities and 30 disabled participants located Pattani, Yala and Narathiwat provinces, who were willing to participate in the study. The research instruments were an interview form and a questionnaire to assess the quality of life of persons with disabilities. The data was analyzed using content analysis and SWOT analysis. The results found that the area-based mechanism for empowerment persons with disabilities was succeeded with the collaboration among the government offices, agencies and local people. The process started from the training of area-based mechanism, doing case management to access the information including (1) interview for services, (2) building cooperation in services, (3) reporting and recording the cases, and doing the individual plan to improve the quality of life of persons with disabilities including the process of supervision, monitoring and evaluation. Moreover, the study found that doing the individual plan should divide persons with disabilities into 2 groups: 1) persons with disabilities who need help should focus on the areas of adjustment to their disabilities such as counseling, the survey to find their needs of accessibility and the guideline for the government agencies to provide assistance that fits with the area context and 2) the successful persons with disabilities should focus on the development of their capability, their family supports and participation in the community network.